DYNAMICS OF LAND USE AND LAND COVER IN JARI (RS) AND SOYBEAN EXPANSION SCENARIOS BETWEEN 2025-2030 - Beilfuss, Eric Moisés; Petsch, Carina; Trentin, Romario (Ra'e Ga: o Espaço Geográfico em Análise, 2024)
In recent decades, the Pampa Biome has rapidly transitioned from grasslands to soybean crops. This article aims to simulate soybean expansion in Jari (RS), Brazil, between 2025 and 2030. Methodologically, the software Dinamica EGO was used. The dynamic data entered refers to the land use and land cover from the MapBiomas 8.1 project for the years 2000 and 2022. The static data refers to altitude, slope, landforms and soils. The results showed 33% increase in the area under soybean cultivation between 2000 and 2022, with a significant reduction in the significant reduction in grassland areas. The probability of transition from grassland to soybean crops is higher close to areas with a mosaic of uses, and smaller near forested areas. The Dinamica EGO showed an overall accuracy of 65.6%, comparing the real map with the simulated map for the year 2022. It should be noted that the software had greater difficulty in estimating small soybean crops, which were planted on land less suitable for cultivation, such as steeper slopes. In this way, the projections indicate a continued increase in the area of soybean cultivation by 2030, covering 51% of the municipality's area, mainly due to the replacement of natural grassland areas. Therefore, it is crucial to continue monitoring the expansion of soybean in the Pampa Biome.